0834 Different Neural Circuits Were Associated With Different Parts of Relationships Among Sleep, Pain and Anxiety in Women with Primary Dysmenorrhoea. (27th May 2020) - Chein, K; Wei, S; Hung, C; Tu, C; Hsieh, J
Abstract: Introduction: Although the relationships amongst sleep, pain and anxiety have been evidenced, the underlying neurological mechanisms remain elusive. Primary dysmenorrhea is a good model of spontaneous pain with clear painful (menstruation, state ) and pain free (e.g., peri-ovulatory phase, trait ) conditions. We sought to investigate the state - and trait -related neural signatures that link sleep and anxiety in primary dysmenorrhea. Methods: Thirty female subjects with primary dysmenorrhea and 30 healthy female controls completed resting-state functional magnetic resonance imaging, the State-Trait Anxiety Inventory and sleep quality assessments during menstruation and peri-ovulatory phases. As we have reported that there was altered default mode network in the primary dysmenorrhea, posterior parietal cortex (PPC) was therefore chosen as the seed to elucidate the functional connectivity that may correlate with sleep and anxiety. Results: The primary dysmenorrheic subjects exhibited sleep disturbances throughout the menstrual cycle with increased state anxiety. The primary dysmenorrheic subjects demonstrated significantly higher correlations between the sleep quality and the PPC-insula and -putamen functional connectivity during the peri-ovulatory phase. During menstruation, the primary dysmenorrheic subjects demonstrated significantly lower correlations between their state -anxiety scores and the PPC-occipital cortex functional connectivity. Conclusion: After regressing out the effects of trait anxiety, the correlation between sleep quality and the PPC-putamen functional connectivity was not significant, indicating anxiety-mediated sleep-pain relationship. The PPC-insula functional connectivity, by contrast, was remained significant. Furthermore, state anxiety was associated with the PPC-occipital cortex functional connectivity that was significantly impaired in primary dysmenorrheic subjects. These findings hinted pain and anxiety mediating sleep quality in different neurological circuits. Support: Taipei City Goverment(10401-62-046 and 10501-62-046)